THE CONCEPT OF CHILD EDUCATION IN A HARMONIOUS FAMILY ACCORDING TO WAHBAH ZUHAYLI AND ABDULLAH NASHIH ULWAN - Agustini, Sri (Tawazun: Jurnal Pendidikan Islam, 2019)
This paper aims to explore the concept of child education in a harmonious family according to Wahbah Zuhayli and Abdullah Nashih Ulwan and analyze the concept of child education in a harmonious family according to the Islamic perspective. Wahbah Zuhayli emphasized on the fact that in families there are children whose education needs to be noted. Educational materials to teach to children are about faith (aqidah), physical education, religious practices, linguistics, character, spiritual education, social skills, hard skills, emotional skills, intellectual skills, health, aesthetics and sexual education. Abdullah Nashih Ulwan emphasized on child education about faith, moral (character), physical education, rational thinking (reason), psychology, social skills, and sexual education. The application used the are through providing examples, customs, advice, attention/supervision and punishment. Islamic Perspective is a complex and thorough education. Education lasts from birth until death, making education something very important, especially from parent to child, and the child unto himself or herself. Everything that is taught should be in accordance with the Quraan and hadith and must not violate the laws and the knowledge itself must not be deviant. The application must be as in ways or methods exemplified by the Qur'an and the Prophet Muhammad PBUH.